The Global Impact of the Systemic Economies and MENA Business Cycles - Cashin, Paul.; Mohaddes, Kamiar; Raissi, Mehdi (Washington, D.C. : International Monetary Fund, 2012)
This paper analyzes spillovers from macroeconomic shocks in systemic economies (China, the Euro Area, and the United States) to the Middle East and North Africa (MENA) region as well as outward spillovers from a GDP shock in the Gulf Cooperation Council (GCC) countries and MENA oil exporters to the rest of the world. This analysis is based on a Global Vector Autoregression (GVAR) model, estimated for 38 countries/regions over the period 1979Q2 to 2011Q2. Spillovers are transmitted across economies via trade, financial, and commodity price linkages. The results show that the MENA countries are more sensitive to developments in China than to shocks in the Euro Area or the United States, in line with the direction of evolving trade patterns and the emergence of China as a key driver of the global economy. Outward spillovers from the GCC region and MENA oil exporters are likely to be stronger in their immediate geographical proximity, but also have global implications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet